2014
DOI: 10.1007/s11325-014-0945-5
|View full text |Cite
|
Sign up to set email alerts
|

Side effects to continuous positive airway pressure treatment for obstructive sleep apnoea: changes over time and association to adherence

Abstract: While some side effects are related to adherence, most are not. Not all side effects are stable over time. This, together with differences in methodology between studies, might explain the conflicting findings in earlier research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 25 publications
2
54
0
4
Order By: Relevance
“…Moreover, one of the side effects of the use of a continuous positive airway pressure device (common choice of therapy in treating pediatric OSA) is oral and nasal dryness. 16 Several studies have demonstrated that people who mouth breathe face increased risk of dental caries, gingivitis, and other oral infection. 39 Interestingly, adenotonsillar hypertrophy (reflected by Brodsky score of II or more) was a positive predictor for dental caries and gingival bleeding in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, one of the side effects of the use of a continuous positive airway pressure device (common choice of therapy in treating pediatric OSA) is oral and nasal dryness. 16 Several studies have demonstrated that people who mouth breathe face increased risk of dental caries, gingivitis, and other oral infection. 39 Interestingly, adenotonsillar hypertrophy (reflected by Brodsky score of II or more) was a positive predictor for dental caries and gingival bleeding in our study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Dry mouth can also occur during treatment of patients with OSA using continuous positive airway pressure devices. 16 Tsuda et al reported that 40% of adults on continuous positive airway pressure for OSA have poor oral health. 17 Moreover, recent studies have shown that OSA can activate various inflammatory processes, which when coupled with a dry mouth,…”
Section: Introductionmentioning
confidence: 99%
“…Early side-effects related to CPAP such as increased number of awakenings and dry mouth after 1-2 weeks are significantly associated to treatment dropout during the first year and machine usage time after six months. [8] Other side-effects, such as blocked nose, skin irritations, mask leaks, [9] and claustrophobia [10] have also been shown to lower adherence. [11] CPAP-treated patients perceive that information about OSAS (e.g., about apneas and sequelae) and CPAP (e.g., side effects) affect adherence to treatment positively, while a lack of support from personnel at the CPAP initiation makes it more difficult for the patient to use CPAP.…”
Section: Introductionmentioning
confidence: 99%
“…
We would like to thank Akar et al for their interest in our study [1], and for their comments on it.Side effect data were collected using SECI (Side Effects to Continuous Positive Airway Pressure (CPAP) Inventory), which is a self-report instrument for CPAP side effects that was developed by our group for a previous study [2]. That is, eye irritation as well as other side effects were reported by the patients, and were not based on an ophthalmological examination.
…”
mentioning
confidence: 96%
“…We would like to thank Akar et al for their interest in our study [1], and for their comments on it.…”
mentioning
confidence: 96%